2019
DOI: 10.3847/2041-8213/ab60b1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Imbalanced Collisionless Alfvén Wave Turbulence with Nonlinear Diffusion Equations

Abstract: A pair of nonlinear diffusion equations in Fourier space is used to study the dynamics of strong Alfvénwave turbulence, from MHD to electron scales. Special attention is paid to the regime of imbalance between the energies of counter-propagating waves commonly observed in the solar wind (SW), especially in regions relatively close to the Sun. In the collisionless regime where dispersive effects arise at scales comparable to or larger than those where dissipation becomes effective, the imbalance produced by a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…No correlation between spectral steepening and cross helicity was found, throwing the influence of alignment on ion-scale steepening further into doubt. Effects of damping on highly imbalanced turbulence may provide insight into the transition range [89]. Though we exclude intervals with coherent waves, the presence of intermittency may affect nonlinear interaction at ion scales [40,47,48,50,90].…”
mentioning
confidence: 99%
“…No correlation between spectral steepening and cross helicity was found, throwing the influence of alignment on ion-scale steepening further into doubt. Effects of damping on highly imbalanced turbulence may provide insight into the transition range [89]. Though we exclude intervals with coherent waves, the presence of intermittency may affect nonlinear interaction at ion scales [40,47,48,50,90].…”
mentioning
confidence: 99%
“…In [118], it is shown that, in the forced case, there is an enhanced inverse transfer of kinetic energy to the large scales. The role of a (generalized) cross-helicity is studied in [119] (see also [120]). It can be seen as allowing for a smooth transition from MHD scales to kinetic scales.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high-resolution spacecraft observations of solar-wind turbulence provide important data for constructing models of energy cascades in Hall-MHD and beyond, such as for instance statistical theories of extended MHD where both the Hall drift and the electron inertia are included to treat length and time scales comparable to the ion cyclotron frequency and/or the electron skin depth [90,118] (see also [119]). These formulations are expected to be useful for modelling inertial confinement by high-intensity lasers in the laboratory, as well as turbulenceplasma waves interactions.…”
Section: Modelling Helical Turbulence For Fluids and Mhdmentioning
confidence: 99%